Performance Analysis of Different Audio Video Codecs for Wireless and Wired VoIP - Nazri Ismail, Mohd; ‘Afizi Shukran, Mohd; Rizal Mohd Isa, Mohd; Adib, Mohd (International Journal of Engineering and Technology, 2018)
This project thesis focuses on quality of voice and video performance in a wired as well as in a wireless network. The analysis was done by using network management system (NMS) to monitor and record the performance of different VoIP codecs in various use cases. Another important challenge is to define the best audio/video codec that can be used in an existing network to satisfy defined QoS parameters. We conclude on our findings that a separation between a wireless and wired environment wasn’t reasonable, because the occurring differences of the QoS metrics were too small to measure with the used setup. During the testing of the different codecs the Speex codec reached the best result compared to the others. It can be said Speex is the codec with the least needed bandwidth utilization and therefore the outcome of the testing must be seen divided.